Whole Genome Analysis of Proteus mirabilis in a Poultry Breeder Farm Reveals the Dissemination of blaNDM and blaCTX-M Mediated by Diverse Mobile Genetic Elements - Haibin Hu; Ke Wu; Tiejun Zhang; Yuhuan Mou; Luya Liu; Xiaoqin Wang; Wei Xu; Wenping Chen; Xiaojiao Chen; Hongning Wang; Changwei Lei (Agriculture, 2025)
Proteus mirabilis is a significant foodborne opportunistic pathogen associated with various nosocomial infections. Chicken farms may serve as an important reservoir for P. mirabilis. However, research on antibiotic resistance and genomic features of P. mirabilis in China’s poultry industry is limited. This study isolates P. mirabilis from a breeder farm in China and investigates the dissemination of P. mirabilis and clinically significant antibiotic resistance genes (ARGs), including blaNDM and blaCTX-M. From 510 samples, 69 isolates were obtained, classified into 11 sequence types (STs), with ST135 and ST175 predominating. A total of 39 ARGs were detected, including fosA3, floR, blaCTX-M-3, blaCTX-M-65, and blaNDM-1. Genetic analysis revealed that blaNDM-1 was exclusively located on Salmonella genomic island 1 (SGI1), while blaCTX-M was found in various mobile genetic elements (MGEs), including Tn7, SXT/R391 integrative conjugative elements (ICEs), Proteus mirabilis genomic resistance island 1 (PmGRI1), and SGI1. Notably, many isolates carried multiple MGEs, suggesting frequent horizontal transfer of ARGs in P. mirabilis. These findings underscore the role of P. mirabilis in carrying and spreading antibiotic resistance, posing significant risks to the poultry industry and public health.